2021
DOI: 10.1111/jocd.14129
|View full text |Cite
|
Sign up to set email alerts
|

National market analysis for body contouring providers: Medical spas and physician practices

Abstract: In recent years, the field of cosmetic medicine has continued to expand, especially with the increasing popularity and availability of minimally and non-invasive treatments. In particular, body contouring modalities have experienced remarkable growth with the advent of techniques that utilize bulk cooling, bulk heating, and electromagnetic muscle stimulation (EMMS). [1][2][3][4][5][6] According to the most recent member survey of the American Society for Dermatologic Surgery (ASDS), there has been a fourfold i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Unsurprisingly, one 2018 study by the American Society for Dermatologic Surgery found an almost fourfold increase in minimally invasive body contouring procedures performed by dermatologists since 2011. 1 Despite its phenomenal rise in popularity, the coronavirus disease 2019 (COVID-19) pandemic is poised to serve as a litmus test to the dermal filler industry's perseverance. Rice et al 2 aimed to evaluate whether there was a shift in demand for dermal fillers in the postpandemic digital environment: their survey found that over 50% of dermatologists indicated a relative increase in cosmetic consultations within their practices despite the limitations on in-person office visits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, one 2018 study by the American Society for Dermatologic Surgery found an almost fourfold increase in minimally invasive body contouring procedures performed by dermatologists since 2011. 1 Despite its phenomenal rise in popularity, the coronavirus disease 2019 (COVID-19) pandemic is poised to serve as a litmus test to the dermal filler industry's perseverance. Rice et al 2 aimed to evaluate whether there was a shift in demand for dermal fillers in the postpandemic digital environment: their survey found that over 50% of dermatologists indicated a relative increase in cosmetic consultations within their practices despite the limitations on in-person office visits.…”
Section: Introductionmentioning
confidence: 99%
“…With its steadily growing popularity, patients and clinicians have demanded longer lasting and safer products, incurring a demand for more advanced dermal fillers. Unsurprisingly, one 2018 study by the American Society for Dermatologic Surgery found an almost fourfold increase in minimally invasive body contouring procedures performed by dermatologists since 2011 1 . Despite its phenomenal rise in popularity, the coronavirus disease 2019 (COVID‐19) pandemic is poised to serve as a litmus test to the dermal filler industry's perseverance.…”
Section: Introductionmentioning
confidence: 99%
“…The medical aesthetics industry is a very pro table and rapidly growing branch of medicine both internationally and locally (13)(14)(15)(16)(17). Reports (10,(18)(19)(20) emerging from international countries that have regulated the practice of somatologists are highlighting the dangers and increase in litigation associated with these practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…Although it can be challenging to treat, newer and novel laser and energy-based devices have emerged that offer increased versatility for patients, which have contributed to the recent expansion of the body treatment market. 1 Such technologies include vacuum-assisted subcision (Cellfina; Ulthera, Mesa, AZ), combination infrared and bipolar radiofrequency energy with vacuum (VelaShape; Candela, Marlborough, MA), 1440 nm Nd:YAG laser with a side-firing fiber and temperature-sensing cannula (Cellulaze; Cynosure, Westford, MA), and rapid acoustic pulse technology (Resonic; Soliton, Houston, TX), among others. More recently, cellulite has become an emerging concern, especially since technology has evolved to target this condition more safely and effectively.…”
mentioning
confidence: 99%